New second-stage concentrators (XX SMS) for parabolic primaries; Comparison with conventional parabolic trough concentrators - Canavarro, Diogo (2015)
Parabolic Trough concentrators are the predominant Concentrated Solar Power (CSP) technology today. However this technology is facing substantial challenge from the need to reduce costs and/or increase performance. This paper address this challenge by exploring the room left from the fact this type of optic falls short from the theoretical limits of concentration, proposing a new solution enabling the design of larger troughs with higher concentration or larger acceptance angles, through the use of second stage concentration of a novel type. This new optic is designed with the Simultaneous Multiple Surface (SMS) method for two reflective (X) surfaces (XX SMS) Winston et al. (2005) – of which the primary is approximately parabolic – using a different assignation of the edge rays in order to significantly reduce the Fresnel losses around the glass cover of the evacuated tubes commonly used in CSP applications. To analyze the merits of this new optic, two different comparisons are made. The first one with the SMS Helmet concentrator through the calculation of CAP (Concentration–Acceptance Product) and the second one with a commercial Parabolic Trough concentrator, using an estimate of the total amount of collected energy (kW h) for one particular location, Faro (Portugal). The paper ends with a discussion of the results obtained, their impact and possible applications in the future.